2019
DOI: 10.2147/idr.s210961
|View full text |Cite
|
Sign up to set email alerts
|

<p>Molecular epidemiology and antimicrobial resistance of invasive non-typhoidal <em>Salmonella</em> in China, 2007–2016</p>

Abstract: PurposeHuman infections caused by invasive non-typhoidal Salmonella (iNTS) are highly prevalent worldwide. However, data for such infections in China are scarce. This study reports the epidemiology of iNTS in China.MethodsINTS isolates were recovered from blood and other clinical specimens collected during 2007–2016 across five provinces (Shanghai, Xinjiang, Fujian, Guangxi, and Chongqing) in China. Antimicrobial susceptibility was performed using the agar dilution method and molecular epidemiology was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 39 publications
5
32
2
Order By: Relevance
“…An increasing prevalence of antimicrobial resistance has been observed in NTS over recent decades [41]. A substantial amount of resistance to antibiotics used for NTS infections was found in the present study, and accompanied with a upward trends over the years; 81.3% of isolates were resistant to at least one of the first-line agents, and more than half (52.4%) of isolates were resistant to two or more first-line agents.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 62%
“…An increasing prevalence of antimicrobial resistance has been observed in NTS over recent decades [41]. A substantial amount of resistance to antibiotics used for NTS infections was found in the present study, and accompanied with a upward trends over the years; 81.3% of isolates were resistant to at least one of the first-line agents, and more than half (52.4%) of isolates were resistant to two or more first-line agents.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 62%
“…The qepA gene was previously detected in Salmonella spp. from patients with diarrhea in China, but it was absent from isolates collected from patients with diarrhea in this study (46). The copresence of the qnrB and qnrS genes, the oqxA and oqxB genes, and the qepA gene in a single Salmonella isolate is seldom reported in Europe (63).…”
Section: Discussionmentioning
confidence: 48%
“…A study of a total of 178 isolates related to human infections caused by invasive Salmonella spp. collected in five provinces of China between 2007 and 2016 revealed that 53.4% of the isolates were MDR (46). The high rates of MDR among Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%
“…In severe cases of salmonellosis, antibiotics are typically prescribed for treatment; however, the emergence of multidrug-resistant (MDR) S. enterica strains has raised global concern, due to an increase in the mortality rate of infected patients ( Gong et al, 2019 ; Zhan et al, 2019 ). In particular, extended-spectrum beta-lactamase-producing Salmonella strains have been frequently isolated from food animals in many countries ( Zhao et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%